Menggereja Murah Hati : Sebuah Model Pastoral Ekklesiologis Berbasis Pemulihan Trauma - Batubara, Jhon Piter; Nadeak, Marthin; Munthe, Marthin Pangambatan; Pane, Sofian Mangaraja Belang (Sekolah Tinggi Teologi Sumatera Utara, 2023)
This article wants to show the legalistic approach taken by the church in responding to behavior that is considered wrong by the congregation. From the author's perspective, such an approach is not relevant in the current situation as an effort to guide the congregation to goodness. In fact, it is very likely that a trend like this will cause trauma for the congregation. This study uses the qualitative-descriptive method, namely with Trauma Informed Pastoral Care (TIPC) approach to understand the concept of